Electrogenerated N‐Heterocyclic Carbene in Ionic Liquid: An Insight into the Mechanism of the Oxidative Esterification of Aromatic Aldehydes. Issue 8 (9th April 2014) - Forte, Gianpiero; Chiarotto, Isabella; Inesi, Achille; Loreto, Maria Antonietta; Feroci, Marta
Abstract An N‐heterocyclic carbene (NHC), generated by cathodic reduction of BMIm BF4, mediates the oxidative esterification of aromatic aldehydes with organic bromides in the corresponding ionic liquid as solvent. The product recovery by simple extractive work‐up with diethyl ether allowed the ionic liquid to be recycled up to 9 times for subsequent electrolyses, with no significant loss in the product yield. The isolation of an intermediate, whose structure was confirmed by synthesis and transformation into the ester, provided the key for a mechanistic insight into the reaction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>